Identification of an inhibitor for atherosclerotic enzyme NOX-1 to inhibit ROS production - Rik Ganguly; Angneh Ngoruh; Prosperwell Ingty; Shashi Kumar Yadav; Atanu Bhattacharjee (SpringerOpen, 2023)
Abstract Background NOX-1 overexpression has been observed in various studies, persons with diabetes or cardiovascular conditions. NOX-1 orchestrates the disease pathogenesis of various cardiovascular conditions such as atherosclerotic plaque development and is a very crucial biomarker. Therefore, this study was carried out to deduce the three-dimensional modelled structure of NOX-1 using DeepMind AlphaFold-2 to find meaningful insight into the structural biology. Extensive in silico approaches have been used to determine the active pocket, virtually screen large chemical space to identify potential inhibitors. The role of the key amino acid residues was also deduced using alanine scanning mutagenesis contributing to the catalytic process and to the overall stability of NOX-1. Results The modelled structure of NOX-1 protein was validated using ERRAT. The ERRAT statistics with 9 amino acids sliding window have shown a confidence score of 96.937%. According to the Ramachandran statistics, 96.60% of the residues lie within the most favoured region, and 2.80% of residues lie in the additionally allowed region, which gives an overall of 99.4% residues in the three quadrants in the plot. GKT-831 which is a referral drug in this study has shown a GOLD interaction score of 62.12 with respect to the lead molecule zinc000059139266 which has shown a higher GOLD score of 78.07. Alanine scanning mutagenesis studies has shown that Phe201, Leu98 and Leu76 are found to be the key interacting residues in hydrophobic interactions. Similarly, Tyr324, Arg287 and Cys73 are major amino acid residues in the hydrogen bond interactions. Conclusions NOX-1 overexpression leads to heightened ROS production resulting in catastrophic outcomes. The modelled structure of NOX-1 has a good stereochemistry with respect to Ramachandran plot. The lead molecule zinc000059139266 has shown to have a very high interaction score of 78.07 compared to the referral drug GKT-831 with a score of 62.12. There is an excellent scope for the lead molecule to progress further into in vitro and in vivo studies.